Strategies for students’ well-being development: the task-oriented classroom approach - Wahyuni, Esa Nur; Maksum, Ali; Aziz, Rahmat; Mangestuti, Retno (Institute of Advanced Engineering and Science, 2025)
Promoting students’ well-being is a vital aspect of education. Creating a conducive classroom learning environment is essential, and task orientation plays a significant role. This paper aims to explore three research objectives related to the influence of the learning environment on student well-being by focusing on creating a task-oriented learning environment. The study employs a quantitative approach with a cross-sectional study design. The study analyzed 1,698 students (676 male and 994 female students) from nine cities in East Java, Indonesia. The results of the simultaneous regression analysis showed that R=.578, R2=.334, and p<.10. The learning environment was found to predict student well-being by 33.4% significantly. At the same time, task orientation was identified as the most dominant factor affecting student well-being. The study’s findings suggest that task orientation could be a solution to enhance student well-being in classroom learning practices. This study suggests the need for teacher development to improve teachers’ professional ability to facilitate learning in the classroom. Future research should consider using central variables, including moderating and intervening variables, to explore the relationship between the learning environment and student well-being.